Creativity and writing with generative artificial intelligence in the master’s degree in teacher training - Rovira-Collado, José; Miras, Sebastián; Mateo-Guillen, Copelia; Ruiz-Bañuls, Mónica (Frontiers in Education, 2025)
The creative possibilities of Generative Artificial Intelligence (GenAI) are transforming writing processes across all educational levels. Since the emergence of OpenAI in 2022, multiple experiences and perspectives have emerged regarding the integration of GenAI in language and literature classrooms. These tools are reshaping traditional writing practices, opening new pathways to foster students’ creativity, enhance critical thinking, and collaborative learning. This study analyzes the integration of GenAI over three academic years (2022–2023, 2023–2024, and 2024–2025) in the training of future Spanish Language and Literature teachers in Secondary Education. Specifically, it focuses on the course Research, Innovation, and Use of ICTs in the Teaching of Language and Literature, part of the Master’s Degree in Secondary Education at the University of Alicante. Students’ work is organized through a classroom blog (https://didacticalenguayliteraturaua2025.blogspot.com/,https://didacticalenguayliteraturaua2024.blogspot.com/, and https://didacticalenguayliteraturaua2023.blogspot.com/) and a dedicated social media hashtag for each academic year (#INVTICUA23, #INVTICUA24, and #INVTICUA25), allowing them to share work openly and interactively. The research employs a mixed-methods approach. First, a quantitative study was conducted using questionnaires at the beginning and end of the course to analyze students’ learning about GenAI. A total of 118 participants (from #INVTICUA24 and #INVTICUA25) took part. Second, the process of introducing and integrating GenAI into established teaching activities is described, followed by a qualitative content analysis of students’ work. Key activities include: (A) blog post writing with GenAI, examining how the tool assists in drafting weekly entries and types of errors generated; (B) I Couldn’t Do This Without AI, a collaborative activity where students design a teaching proposal using an AI tool for Secondary Education classrooms; and (C) Education 2050 Stories, a creative writing exercise imagining the future of education using ChatGPT. Across all activities, students initially demonstrated limited knowledge of GenAI but progressively developed specific skills related to its educational use. Results confirm students’ growing interest in these tools and reveal a consolidated learning process over the academic years. While these practices represent a novel approach and an opportunity for educational innovation, the ultimate goal is to normalize GenAI integration as a regular component of teacher training programs.